The high concentration of Arg213 → Gly extracellular superoxide dismutase (EC-SOD) in plasma is caused by a reduction of both heparin and collagen affinities - Petersen, Steen V.; Olsen, Dorte Aa.; Kenney, John M.; Oury, Tim D.; Valnickova, Zuzana; Thogersen, Ida B.; Crapo, James D.; Enghild, Jan J. (East Carolina University, 2005)
The C-terminal region of EC-SOD (extracellular superoxide dismutase) mediates the binding to both heparin/heparan sulphate and type I collagen. A mutation (Arg213→Gly; R213G) within this extracellular matrix-binding region has recently been implicated in the development of heart disease. This relatively common mutation affects the heparin affinity, and the concentration of EC-SOD in the plasma of R213G homozygous individuals is increased 10- to 30-fold. In the present study we confirm, using R213G EC-SOD purified from a homozygous individual, that the heparin affinity is reduced. Significantly, the collagen affinity of the R213G EC-SOD variant was similarly affected and both the heparin and collagen affinitieswere reduced by 12-fold. Structural analysis of synthetic extracellularmatrix-binding regions suggests that the mutation alters the secondary structure.We conclude that the increased concentration of EC-SOD in the plasma of R213G carriers is caused by a reduction in both heparin and collagen affinities. Originally published Biochemical Journal, Vol. 385, No. 2, Jan 2005
Keywords: Collagen; Extracellular superoxide dismutase (EC-SOD); Oxidative damage; Reduced afficity; R213G; Structures